Impact of Project Scheduling Tools on Resource Optimization in Manufacturing Projects in Rwanda - Sehene, Samuel (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the impact of project scheduling tools on resource optimization in manufacturing projects in the Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that the use of project scheduling tools significantly enhances resource optimization in manufacturing projects by improving efficiency and reducing waste. These tools enable project managers to allocate resources more effectively, allowing for better tracking of tasks and timelines, which minimizes idle time and maximizes productivity. Research indicates that project scheduling software facilitates real-time data sharing and communication among team members, leading to informed decision-making and timely adjustments to project plans. By analyzing workload distribution, these tools also help identify bottlenecks and underutilized resources, allowing managers to redistribute tasks and optimize labor utilization. Ultimately, the integration of project scheduling tools in manufacturing not only streamlines operations but also contributes to cost savings and improved overall project outcomes. Implications to Theory, Practice and Policy: Resource-based view (RBV) theory, theory of constraints (TOC) and agile project management theory may be used to anchor future studies on assessing the impact of project scheduling tools on resource optimization in manufacturing projects in Rwanda. Manufacturing firms should invest in customized training programs for project managers and teams to maximize the effectiveness of project scheduling tools. Policymakers should consider creating frameworks that encourage the adoption of advanced project scheduling tools in the manufacturing sector.